Immune Responses to RHAMM in Patients with Acute Myeloid Leukemia after Chemotherapy and Allogeneic Stem Cell Transplantation. (6th June 2012) - Casalegno-Garduño, R.; Meier, C.; Schmitt, A.; Spitschak, A.; Hilgendorf, I.; Rohde, S.; Hirt, C.; Freund, M.; Pützer, B. M.; Schmitt, M.
Abstract : Leukemic blasts overexpress immunogenic antigens, so-called leukemia-associated antigens like the receptor for hyaluronan acid-mediated motility (RHAMM). Persistent RHAMM expression and decreasing CD8 + T-cell responses to RHAMM in the framework of allogeneic stem cell transplantation or chemotherapy alone might indicate the immune escape of leukemia cells. In the present study, we analyzed the expression of RHAMM in 48 patients suffering from acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Furthermore, we correlated transcripts with the clinical course of the disease before and after treatment. Real-time quantitative reverse transcriptase polymerase chain reaction was performed from RNA of peripheral blood mononuclear cells. T cell responses against RHAMM were assessed by tetramer staining (flow cytometry) and enzyme-linked immunospot (ELISPOT) assays. Results were correlated with the clinical outcome of patients. The results of the present study showed that almost 60% of the patients were RHAMM positive; specific T-cells recognizing RHAMM could be detected, but they were nonfunctional in terms of interferon gamma or granzyme B release as demonstrated by ELISPOT assays. Immunotherapies like peptide vaccination or adoptive transfer of RHAMM-specific T cells might improve the immune response and the outcome of AML/MDS patients.